AGRICULTURAL AND FOOD PRODUCTS CONTROL AND ITS EFFECTS ON COMPETITIVENESS - Savić, Mirjana; Kanački, Lidija; Kanački, Zdenko (Economics of Agriculture, 2006)
In economic developed countries, like European Union (EU), food safety is one of the topics that deserve special attention. It is well known fact that international trade is growing and that inter-connection of national economies is rising, so food safety and quality of products adjustment is becoming more significant for participants in international trade. This is especially important for Serbia, which is in the begging of accession process to European Union and World Trade Organization. In the course of Serbian efforts to join WTO and EU, Serbian must compile given action and activities in the area of quality and food safety, to enable economy and society to take part in competitiveness race based on "quality2. This paper emphasis the link between food safety and competitiveness of agricultural and food products, and its influence on specific part of food safety system in Serbia regarding to competitiveness.